2015
DOI: 10.1080/00665983.2015.1027871
|View full text |Cite
|
Sign up to set email alerts
|

Foxes and Badgers in Anglo-Saxon Life and Landscape

Abstract: Anglo-Saxon England (c. AD 410-1066) had a diversity of wild animals, yet the majority of studies to date have focused on a select group of species. These include those considered edible, such as roe and red deer (cervids), and those now extinct in England, such as wolves and beavers. Accordingly, the roles and relations of many other wild mammal species have rarely been studied and are poorly understood. This paper explores human perceptions of, and interactions with, two native species: the fox and the badge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…It decreases in period 3 when chicken increases dramatically and humans are likely to have developed better means of protecting them. This is consistent with a study of Anglo-Saxon fauna, which identified no direct correlation between chicken and fox (Poole 2015). Poole (2015) suggested that, in these instances, humans may have been reducing the fox population as a threat to human infant burials.…”
Section: Recovery Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…It decreases in period 3 when chicken increases dramatically and humans are likely to have developed better means of protecting them. This is consistent with a study of Anglo-Saxon fauna, which identified no direct correlation between chicken and fox (Poole 2015). Poole (2015) suggested that, in these instances, humans may have been reducing the fox population as a threat to human infant burials.…”
Section: Recovery Methodssupporting
confidence: 89%
“…This is consistent with a study of Anglo-Saxon fauna, which identified no direct correlation between chicken and fox (Poole 2015). Poole (2015) suggested that, in these instances, humans may have been reducing the fox population as a threat to human infant burials.…”
Section: Recovery Methodssupporting
confidence: 89%
“…The reasons are several: the main one is that only the larger or more charismatic species have places named after them (Cox et al 2002), meaning that only the historical presence of some mammals and birds can be inferred from toponyms. Aybes and Yalden (1995) mapped historical wolf (Canis lupus) and beaver (Castor fiber) distributions in Britain from place names only, while Poole (2015) used toponyms together with bones and other remains found at archaeological sites to infer the past presence of foxes (Vulpes vuples) and badgers (Meles meles). The latter approach was used by Boisseau and Yalden (1998) to reconstruct the crane (Grus grus) presence in the UK and they also demonstrated that this bird used to nest in England.…”
Section: Introductionmentioning
confidence: 99%
“…This manuscript includes many Old English riddle-poems: number 15 tells the story of a heroic animal that lives underground in a hill, fighting and defending its family against digging invaders. 90 In the sixteenth century, the Tudors legally designated badgers as 'vermin'-nuisance animals-placing a generous bounty of twelve old pence per head. 91 Understandings of vermin at this time were significantly different to our own: while such animals were associated with disease, prior to germ theory this was via theories of 'miasma' and beliefs about witchcraft.…”
Section: The Great British Badger Debatementioning
confidence: 99%